Practical Treatment Options for Chronic Pain in Children and Adolescents An Interdisciplinary Therapy Manual - Dobe, Michael.; Zernikow, Boris. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Pain is an increasingly common symptom in children and adolescents. Once a chronic pain condition affects different aspects of a childs life, it is considered a pain disorder, irrespective of the underlying physical condition. Nearly 5% of the paediatric population now suffer from severe chronic pain conditions. The treatment of pain disorders in childhood and adolescence is complex and needs to address a variety of influencing bio-psycho-social factors. Misconceptions like one of the "Three Thougt Traps" on the part of doctors, therapists and parents also have to be taken into account. This manual describes the inpatient treatment programme of one of the worlds largest treatment facility for chronic pain in children The German Paediatric Pain Centre and the guidance provided is also applicable to outpatient pain management. Epidemiology, aetiology, diagnostics and treatment principles are all examined in detail. Criteria for inpatient treatment are explained, and the structure and organisation of a tertiary treatment centre for chronic pain are described. Therapeutic interventions like dealing with "Black Thoughts", "Distraction-ABC", "Stress Day" and the "Pain ProvocationTechnique" are presented with the aid of many examples of pain management and health care from clinical practice. Special features of pain therapy for children and adolescents suffering from comorbid mental disorders, family difficulties or physical complaints are also discussed.